Patient’s Waiting Time at Emergency Department in a Selected Tertiary Level Hospital - Ali, ASM Zulfiquer; Zafreen, Farzana; Al Azad, Md Abdus Samad; Hossain, AKM Alamgir; Akter, Jesmin (Journal of Armed Forces Medical College, Bangladesh, 2019)
Introduction: Patient satisfaction is one of the principal aims of the healthcare delivery system. Waiting time is an important parameter for assessment of hospital management and influences patient satisfaction. Patient waiting time reflects the effectiveness of treatment and management of the hospital. Objective: To find out the waiting time of patient attending the Emergency Department in a selected tertiary level hospital and to identify the factors related to waiting time, socio-demographic characteristics of the patient and patients satisfaction status about waiting time. Materials and Methods: This descriptive cross-sectional study was conducted at emergency department of Dhaka Medical College Hospital from March 2011 to June 2011. A total of 115 cases were selected through systemic random sampling. Self-administered structured questionnaire was used for data collection. Results: Mean waiting time was 10.17 ± 5.17 minutes. Patients waiting time was significantly (p < 0.001) associated with type of emergency. Out of 115 respondents, 30.4% received treatment within 5 minutes and only 17.4% waited more than 15 minutes. Patients waited more than 15 minutes at obstetric, medical, surgical and gynaecological emergency were 4.2%, 8.8%, 25.0% and 35.3% respectively. Most (72.1%) of the patients found satisfied with waiting time at emergency and only 27.8% expressed their dissatisfaction. Conclusion: In this study patients’ waiting time was associated with type of emergency and most of the patients were satisfied with the waiting time at Emergency Department. Journal of Armed Forces Medical College Bangladesh Vol.13(2) 2017: 32-34